Investigation of spinal posture signatures and ground reaction forces during landing in elite female gymnasts - Wade, M.; Campbell, A. C.; Smith, A.; Norcott, J.; O`Sullivan, P. (Journal of Applied Biomechanics, 2012)
The link between static and dynamic landing lumbar postures, when gymnasts are exposed to large ground reaction forces, has not been established. This investigation aimed to (a) determine if a relationship exists between sagittal static and dynamic landing lumbar spine angles at peak ground reaction force (GRF) and (b) quantify how close to end-range postures the gymnasts were at landing peak GRF. Twenty-one female gymnasts` upper and lower lumbar spine angles were recorded: statically in sitting and standing, during landing of three gymnastic skills, and during active end-range lumbar flexion. Pearson`s correlations were used to investigate relationships between the angles in different postures. Significant correlations (r = .77-.89, p < .01) were found between all the static/dynamic postures in the lower lumbar spine angle, while fewer and less significant upper lumbar spine correlations were reported. Thirty percent of gymnasts landed a backsault with their lower lumbar spine flexed beyond their active end-range while experiencing GRF 6.8-13.3 times their body weight. These results inform low back pain prevention and management strategies in this population and highlight areas for future research.